Serum myoglobin and creatine kinase enzymes in acute myocardial infarction treated with Anistreplase. - McCullough, D. A. (1992)
AIMS: To compare plasma myoglobin concentration and cardiac enzyme activity with electrocardiographic (ECG) changes in two groups of patients (reperfused and non-reperfused) participating in a placebo-controlled randomised double blind trial of treatment of myocardial infarction (MI) with intravenous thrombolytic therapy (Anistreplase). METHODS: Twenty two patients with confirmed MI obeying strict inclusion and exclusion criteria were studied. Plasma myoglobin was measured by radioimmunoassay and creatine kinase enzyme (CK and CKMB) by NAC activated and NAC activated/immunoinhibition methods respectively in all patients before and at frequent intervals after injection of Anistreplase or placebo. Patients were divided into reperfused (R) and non-reperfused (NR) groups on the basis of ECG criteria. Reperfusion was diagnosed if the measured ST segment elevation fell by greater than or equal to 50% at 2 hours post dosing. RESULTS: The time to peak (TTP) myoglobin was significantly less in the R group compared with the NR group but there was considerable overlap in the range of values. The area under the enzyme time curves (AUCs) and summed ST segment epsilon ST elevations were significantly smaller in the R compared with the NR group. CONCLUSIONS: Although TTP myoglobin results were significantly lower in the R group, TTP myoglobin will probably not be useful as an non-invasive indicator of reperfusion because of the overlap in values between the two groups. The significant reduction in the AUC and epsilon ST only in the R group suggests decreased infarct size. However, in this small preliminary study reperfusion did not occur more frequently with Anistreplase than without.